Evaluating and implementing transport measures in a wider policy context : the 'Civilising Cities' initiative - Jones, P; Lucas, K; Whittles, M (Elsevier, 2003)
In the UK, local authority transport departments are being encouraged to implement transport schemes that can contribute cost-effectively to achieving a wide range of corporate policy objectives. The 'Civilising Cities' initiative, funded by the UK's RAC Foundation and the Department for Transport, seeks to identify - through a set of Pilot Projects - how packages of transport measures (usually in partnership with initiatives from other agencies) can contribute to improving local quality of life. One key feature of the project has been the development of a comprehensive Indicator Framework for cross-sector evaluation, that has defined a set of indicators covering nine areas of quality of life: neighbourhood, environment, transport, health, education, local economy, crime, participation and lifestyle. The paper outlines the philosophy behind the project, the range of policy instruments being examined and describes the Indicator Framework and its application.